Optimal Pain Management for the Dental Team - Renton, Tara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is a concise guide to the correct diagnosis and management of dental pain and anxiety. It covers psychology theories about pain, dentine sensitivity, hypersensitivity and cracked tooth syndrome. Chronic pain, temporomandibular disorders and local anesthesia are discussed, and optimal medical and perioperative pain management explained. The book is written by leading experts in the field and provides an up to date, pragmatic perspective on optimizing pain and anxiety management in the dental patient. It includes an overview of differential diagnoses of non-odontogenic orofacial pain. As well as meeting the needs of dentists, the book will be a (3z(Bmust read(3y (Bfor whole dental team.s
Intro to Pain -- The Psychology Theories of Pain -- Psychological Interventions for Persistent Pain -- An Overview of Dental Anxiety and its Non-Medical Management -- Medical Management of Anxiety -- Perioperative Pain Management of the Dental Patient -- Optimal Local Anaesthesia for Dentistry -- Temporomandibular Disorder for the General Dental Practitioner -- Chronic Pain and Overview or Differential Diagnoses of Non-Odontogenic Orofacial Pain -- Dental Pain: Dentine Sensitivity, Hypersensitivity and Cracked Tooth Syndrome.
Keywords: Dentistry; Pain medicine; Dentistry; Pain Medicine; Toothache; Dentistry; Pain Management